REVEALED COMPARATIVE ADVANTAGE INDONESIA DI ANTARA ENAM NEGARA PENGEKSPOR TUNA TERBESAR DI ASIA PERIODE 2001 – 2013 - Daniel Force Costner (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2017)
The competitive market requires Indonesia to know the potential of resource management for the welfare of the society and nation. One of the important things is how much potency of Indonesia in marine resources, especially in tuna fishingsector. Judging from the geographical, Indonesia has a very wide sea with diverse marine resources. It is very important to know how much tuna potency of Indonesia and 5 largest tuna exporting countries in Asia.To findthe potential of tuna export, this research adapts a method called Revealed Comparative Advantage (RCA). Using this method, we can findhow much potency of Indonesia in tuna export compared to 5 largest tuna exporting countries in Asia.Analysis result shows that Indonesia has potential in tuna export. From the total of tuna export, Indonesia ranks number one compared to the 5 largest tuna exporting countries in Asia. RCA result of Indonesia towards 5 other tuna exporting countries shows 5,79 which means Indonesia will be better if specialize in the export of tuna.